Structural and Transport Properties of 1T-VSe2 Single Crystal Under High Pressures - Song, Dongqi; Zhou, Ying; Zhang, Min; He, Xinyi; Li, Xinjian (Frontiers in Materials, 2021)
Two-dimensional transition metal dichalcogenide 1T-VSe2 exhibits a unique three-dimensional charge density wave (CDW) order below ∼110 K at ambient pressure, which shows unusual evolution under pressure. Here we report on the high-pressure structural and transport properties of 1T-VSe2 by extending the pressure up to 57.8 GPa, through electrical transport, synchrotron X-ray diffraction (XRD) and Raman scattering measurements, which unravel two critical pressure points. The CDW transition is found to be enhanced under compression at a rate of 16.5 K/GPa up to the first critical pressure PC1 ∼ 12 GPa, at which a structural phase transition from hexagonal P-3m1 to monoclinic C2/m phase takes place. The second critical pressure PC2 ∼ 33 GPa corresponds to another structural transition from monoclinic C2/m to P21/m phase. These findings extend the phase diagram of pressurized 1T-VSe2 and may help to understand pressure tuning of structures in transition metal dichalcogenides.